ID: 25: SOCIAL DETERMINANTS OF PATIENT ANTIBIOTIC MISUSE IN HARYANA, INDIA. Issue 4 (22nd March 2016) - Barker, A; Verhoeven, K; Ahsan, M; Alam, S; Sharma, P; Sengupta, S; Safdar, N
Abstract : Background: Antibiotic resistance is recognized globally as an urgent health crisis. Multidrug resistant organisms lead to deadly hospital and community acquired infections and complicate patients' underlying health issues. In the United States, antibiotic resistance causes 23, 000 deaths and direct healthcare costs of $20 billion a year. In the developing world, the costs are estimated to be even higher. In India alone, antibiotic resistance is responsible for an estimated 58, 000 infant deaths annually. While its severity is agreed upon, the causes and solutions to antibiotic misuse are complex. Antibiotic dispensing laws are poorly enforced in many developing nations, including India. Patient and provider contributions are intertwined, thus confronting the problem requires a better understanding of the motivations of several populations. Methods: We conducted a mixed methods study in the northern state of Haryana, India, between June and August 2015. We qualitatively assessed the antibiotic knowledge and use practices of 20 local community members using semi-structured interviews. We also completed 64 surveys of community members and healthcare workers. Both populations were given the same survey, which focused on the participant's experience obtaining antibiotics as a patient. The interviews and surveys were conducted in English and Hindi, as applicable, by bilingual members of the research team. Interview data was coded for themes using NVivo software, and quantitative survey responses were analyzed in SAS. We used DAGitty software to construct a directed acyclic graph to determine the minimally sufficient adjustment sets needed to block confounders of the relationship between antibiotic knowledge and antibiotic misuse. Results: Over a third of survey participants reported antibiotic misuse, defined as purchasing medication from a pharmacy without a doctor's prescription (36.5%). Furthermore, none of the 20 community member interviewees were able to correctly define antibiotics without prompting. The interviews also revealed that limited health education, inadequate access to a doctor, and poverty all influence patients' antibiotic decision making. Participants with these characteristics were more likely to bypass doctors and seek medical care directly from a pharmacist. The effect of antibiotic knowledge on antibiotic misuse was significant in our pilot survey data, even after adjusting for the variables in the minimally sufficient adjustment set: first vs. fourth quartile of knowledge, OR=72.09, p=0.014; second vs. fourth quartile, OR=44.09, p=0.006. The covariates in the model include age, income, healthcare occupation, education, having a doctor in the family, and having access to a doctor in your local community. Discussion: This study highlights the need for public health education regarding antibiotics and the extensive health implications of their misuse. Local and national governments should consider social factors when enacting future antibiotic policies.